Auralization of High-Order Directional Sources from First-Order RIR Measurements - Markus Zaunschirm; Franck Zagala; Franz Zotter (Applied Sciences, 2020)
Can auralization of a highly directional source in a room succeed if it employs a room impulse response (RIR) measurement or simulation relying on a first-order directional source, only? This contribution presents model and evaluation of a source-and-receiver-directional Ambisonics RIR capture and processing approach (SRD ARIR) based on a small set of responses from a first-order source to a first-order receiver. To enhance the directional resolution, we extend the Ambisonic spatial decomposition method (ASDM) to upscale the first-order resolution of both source and receiver to higher orders. To evaluate the method, a listening experiment was conducted based on first-order SRD-ARIR measurements, into which the higher-order directivity of icosahedral loudspeaker’s (IKO) was inserted as directional source of well-studied perceptual effects. The results show how the proposed method performs and compares to alternative rendering methods based on measurements taken in the same acoustic environment, e.g., multiple-orientation binaural room impulse responses (MOBRIRs) from the physical IKO to the KU-100 dummy head, or higher-order SRD ARIRs from IKO to em32 Eigenmike. For optimal externalization, our experiments exploit the benefits of virtual reality, using a highly realistic visualization on head-mounted-display, and a user interface to report localization by placing interactive visual objects in the virtual space.